Representasi Gender Dalam K-Drama The Judge From Hell: Analisis Semiotika Sosial Dengan Pendekatan Ibnu Hamad - Corina, Salya Elva (Universitas Gajah Putih, 2025)
Gender representation in media, particularly within K-Dramas, reflects shifting social dynamics and the evolving construction of female identity. The Judge from Hell (2024) portrays Kang Bit-na as a female judge endowed with supernatural authority, challenging dominant patriarchal narratives commonly found in Korean mainstream media. This study aims to examine how female representation and power relations are constructed through symbols, narrative structure, and visual elements in the series. Employing a qualitative method grounded in social semiotics and Ibnu Hamad’s discourse analysis model, this research analyzes five high-intensity episodes in which Kang Bit-na plays a central authoritative role. The findings indicate that The Judge from Hell presents a transformative representation of women—from passive figures to authoritative agents who command both legal and supernatural domains. Through the categories of Field of Discourse, Tenor of Discourse, and Mode of Discourse, the series depicts women as holders of moral and structural power, while male characters occupy negotiated or subordinate positions. Visual analysis reinforces this construction through camera framing, color symbolism, body language, and legal performativity. In conclusion, the drama constructs a counter-narrative to patriarchal norms and broadens the meaning of female authority in contemporary Korean cultural contexts